2019
DOI: 10.3389/fimmu.2019.01672
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Function and Diversity of T Cell Repertoire and Distinct Clinical Course in Patients With IL7RA Mutation

Abstract: The alpha subunit of IL-7 receptor (IL7R7α) is critical for the differentiation of T cells, specifically for the development and maintenance of γδT cells. Mutations in IL7RA are associated with Severe Combined Immunodeficiency (SCID). Infants with IL7RA deficiency can be identified through newborn screening program. We aimed at defining the immunological and genetic parameters that are directly affected by the IL7RA mutation on the immune sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Interleukin 7 (IL-7) expression was high in the presence of TSC, and it is known that IL-7 is necessary for thymocyte survival and has an important role in the differentiation of T cells; indeed, mutations in IL-7 gene and its receptor have been implicated in severe combined immunodeficiency. 53,54 Interleukin 8, which is significantly expressed by TSC, is known to be expressed in humans by recent thymic emigrants, 55 as well as microvascular endothelial cells 56 but interestingly is not expressed in mouse thymus. 57 As IL-8 has also been implicated in T-cell recruitment at inflammation sites, 58 it may also play a parallel role in precursor homing within the human thymus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interleukin 7 (IL-7) expression was high in the presence of TSC, and it is known that IL-7 is necessary for thymocyte survival and has an important role in the differentiation of T cells; indeed, mutations in IL-7 gene and its receptor have been implicated in severe combined immunodeficiency. 53,54 Interleukin 8, which is significantly expressed by TSC, is known to be expressed in humans by recent thymic emigrants, 55 as well as microvascular endothelial cells 56 but interestingly is not expressed in mouse thymus. 57 As IL-8 has also been implicated in T-cell recruitment at inflammation sites, 58 it may also play a parallel role in precursor homing within the human thymus.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CCL25 was not expressed by the thymic stromal cells in microdevices; however, the 48 h that the TSC were cultured in the devices may not have been sufficient time to induce its expression. Interleukin 7 (IL‐7) expression was high in the presence of TSC, and it is known that IL‐7 is necessary for thymocyte survival and has an important role in the differentiation of T cells; indeed, mutations in IL‐7 gene and its receptor have been implicated in severe combined immunodeficiency 53,54 . Interleukin 8, which is significantly expressed by TSC, is known to be expressed in humans by recent thymic emigrants, 55 as well as microvascular endothelial cells 56 but interestingly is not expressed in mouse thymus 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for IL7-mediated TRG rearrangement in human thymocytes is more sparse, but it has indeed been demonstrated that IL7R signalling can activate STAT5 [44], which binds to conserved STAT consensus motifs at TRG regulatory regions and drives germline transcription at the locus [78]. Moreover, γδ T cells from patients with instability-inducing mutations in IL7R exhibit an unusually restricted TRG repertoire and reduced activation of STAT5 in response to IL7 stimulation [79], which further supports a role of IL7 in TRG rearrangement during human γδ T cell development. Surprisingly, while knock-out experiments in mice targeting various IL7 pathway components, such as Il7ra, Jak3 and Il2rg, resulted in disrupted γδ T cell development regardless of age [68,80,81], STAT5 deficiency only perturbed Trg rearrangement and γδ T cell differentiation in fetal but not adult mice [76].…”
Section: Regulation Of Trd/trg Rearrangementmentioning
confidence: 99%
“…Graphical presentation of the repertoire was presented using hierarchical tree maps using the Treemap software (www.treemap.com). Shannon's H, which measures the overall diversity in a given population (24), and takes into account the number of unique sequences (richness of the repertoire) and how evenly the sequences are distributed, was calculated using the following formulas:…”
Section: Immune Repertoire Studiesmentioning
confidence: 99%